PENGGUNAAN KUIS DIGITAL DALAM MENINGKATKAN ANTUSIAS BELAJAR SISWA DI SMA NEGERI 3 KOTA BENGKULU - Rahman Hakim, M. Arif; Puspitasari, Desti; Natasya Putri, Meta; Setyani, Indah; Lestari, Meli (Jurnal Ilmu Pendidikan Islam, 2025)
The use of digital quizzes in learning at SMA Negeri 3 Bengkulu City has had a positive impact on student enthusiasm and understanding. Gamification and interactivity elements in digital quizzes increase student engagement, make the material more interesting, and accelerate understanding of the concepts being taught. This research uses a qualitative descriptive method with data collection techniques through observation, interviews and documentation. The research results show that digital quizzes increase students' learning motivation and help them remember the material more easily. However, there are several obstacles in implementation, such as limited access to digital devices and unstable internet connections. In addition, some teachers experience difficulties in integrating technology in learning. Therefore, strategies are needed such as providing digital devices, increasing internet access, and ongoing teacher training. With adequate support, the use of digital quizzes can continue to be developed to improve the quality of learning in schools.